Comparative analysis of Cervical Human Papillomavirus DNA testing and cytological findings among women presenting for “Pap” smear in a Tertiary Health Centre in Northern Nigeria (2016)
Aim: This study was conducted to compare different cytological findings with cervical HPV infection among women presenting for cervical cancer screening in Gombe north-eastern Nigeria. Study Design: It is a hospital based cross-sectional study. Place and Duration of Study: Departments of Obstetrics/Gynaecology and Histopathology Federal Teaching Hospital Gombe (FTHG) Nigeria, between August 2013 and May 2014. Methodology: Two hundred and nine (209) women were subjected to liquid-based cervical cytology and HPV DNA testing. Results: Of the 209 participants, cytological findings were normal in 126 (61.6%) women while 80 (39.0%) had abnormal features. Three (1.4%) respondents had unsatisfactory smears. The observed abnormal cytological features include HPV changes 30 (14.4%), HPV changes with inflammation 2 (1.0%), inflammatory changes alone 36 (17.3%), Low Squamous Intraepithelial Lesion; LSIL 3 (1.4%), High Squamous Intraepithelial Lesion; HSIL 5 (2.4%) and malignant changes 3 (1.4%). Positive HPV DNA testing was detected among 100 (48.1%) of the participants. Almost half 60 (47.6%) of the women with normal cytology were positive for HPV. Among women with cytologically detected HPV changes, only 16 (50%) were also HPV DNA positive. The sensitivity and specificity of cervical cytology in detecting HPV infection was 16.2% and 85.0% respectively. Conclusion: This study reports a very low sensitivity but relatively high specificity of cytology in detecting cervical HPV infection. It further justifies the need for introduction of HPV DNA testing to improve efficiency and maximise the sensitivity of cytology based cervical cancer screening for women above 30 years.